PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV B UPT SPF SD INPRES BORONG KOTA MAKASSAR - nur annisa; Andi Adam; Rahmatiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
NUR ANNISA, 2025. The Effect of Using Interactive Learning Media on Speaking Skills of Fourth Grade Students of UPT SPF SD Inpres Borong, Makassar City. Thesis. Elementary School Teacher Education Study Program (PGSD S1) Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Advisor 1 Andi Adam and Advisor II Rahmatiah. The formulation of the research problem is "How is the Effect of Using Interactive Learning Media on Speaking Skills of Fourth Grade Students of UPT SPF SD Inpres Borong, Makassar City?". This study aims to determine the effect of using interactive learning media on speaking skills of fourth grade students of UPT SPF SD Inpres Borong, Makassar City. This type of research is quantitative experimental research (pre-experimental design) with a one-group pretest-posttest design. The population used is students of class IV UPT SPF SD Inpres Borong, Makassar City totaling 61 people while the sample used was class IV B students totaling 28 people. The instruments used to collect data were observation, tests and documentation. The results of the study showed that interactive learning media had an effect on the speaking skills of students of class IV B UPT SPF SD Inpres Borong, Makassar City, which can be seen from the comparison of the pretest and posttest results. The average pretest score was 60.71 using the test instrument. The very low category is 0%, After implementing interactive media, the average posttest score was 80.89, students' speaking ability was categorized as high by looking at the scores obtained, namely very high 21.43%, high 32.14%, moderate 46.43%, low 0%, and very low at 0%. The calculation results with t-test analysis after calculating tCount = 8.017 and tTable 2.052 then Tcount 8.017> Ttable 2.052 so it can be concluded that H0 is rejected and H1 is accepted. This means that the use of interactive media in the Indonesian language learning process has an effect on the speaking skills of class IV B UPT SPF SD Inpres Borong Makassar City students. Keywords: Speaking Skills, Interactive Media